Extraction of vanadium from pet-coke gasification cinder: Part 1 leaching kinetics studies in sulphuric acid medium - Das, Shibsundar; Mohanta, Susmita; Kumar, Akshay; Mishra, Devabrata; Sahu, Kamala Kanta (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Petcoke cinder is a solid by-product generated during the gasification of petcoke, accounting for three to five percent of the petroleum coke mass. It commonly contains valuable metals like V, Ni, Al, and Fe, highlighting the resource’s potential for vanadium extraction. Thus, it can be regarded as an emerging secondary source of vanadium and other critical metals. The conventional pyro-cum-hydrometallurgical process for vanadium recovery relied on alkali roasting, which was not only energy-intensive but also contributed to greenhouse gas emissions. Considering environmental concerns and high energy consumption, the current study embodies a state-of-the-art development of an economically viable process for extracting V from petcoke gasification cinders. This paper examines the method of sulfuric acid-leaching of vanadium from gasification cinders and the effects of various parameters, including acid concentration, temperature, process duration, percentage of H2O2, amount of sodium dodecyl sulfate (SDS), and solid-liquid phase ratios. The maximum vanadium yield of 95.62% was achieved under optimal conditions of sulfuric acid concentration, temperature, time, S/L ratio, and amounts of H2O2 and SDS, which were determined to be 4M, 90°C, 3 hours, 20%, and 6%, respectively. The shrinking surface-controlled model was employed to investigate leaching kinetics. The reaction order concerning sulfuric acid concentrations was found to be 1.29. According to the Arrhenius equation, the evaluated apparent activation energy for leaching was approximately 27.67 kJ/mol, and the empirical equation representing the acid leaching kinetics of vanadium is identified as 1-(1-α)1/3 = kt = (9.261 X 103) [H2SO4]1.2916exp[-27674/RT] T.